ChemInform Abstract: Superconductivity in the Narrow‐Gap Semiconductor CsBi4Te6. Issue 3 (21st January 2014) - Malliakas, Christos D.; Chung, Duck Young; Claus, Helmut; Kanatzidis, Mercouri G.
Abstract Centimeter‐sized crystals of the title compound are prepared by reaction of Bi2Te3 with Cs in the vapor phase at 670 °C followed by melting and slow cooling.